Changing paradigm in the treatment of amyloidosis: From disease-modifying drugs to anti-fibril therapy - Quarta, C. Cristina; Fontana, Marianna; Damy, Thibaud; Catini, Julia; Simoneau, Damien; Mercuri, Michele; Garcia-Pavia, Pablo; Maurer, Mathew S.; Palladini, Giovanni (Frontiers in Cardiovascular Medicine, 2022)
Cardiac amyloidosis is a rare, debilitating, and usually fatal disease increasingly recognized in clinical practice despite patients presenting with non-specific symptoms of cardiomyopathy. The current standard of care (SoC) focuses on preventing further amyloid formation and deposition, either with anti-plasma cell dyscrasia (anti-PCD) therapies in light-chain (AL) amyloidosis or stabilizers of transthyretin (TTR) in transthyretin amyloidosis (ATTR). The SoC is supplemented by therapies to treat the complications arising from organ dysfunction; for example, heart failure, arrhythmia, and proteinuria. Advancements in treatments have improved patient survival, especially for those whose disease is detected and for whom treatment is initiated at an early stage. However, there still are many unmet medical needs, particularly for patients with severe disease for whom morbidity and mortality remain high. There currently are no approved treatments to reverse amyloid infiltration and deplete the amyloid fibrils already deposited in organs, which can continue to cause progressive dysfunction. Anti-fibril therapies aimed at removing the deposited fibrils are being investigated for safety and efficacy in improving outcomes for patients with severe disease. However, there is no clinical evidence yet that removing deposited amyloid fibrils will improve organ function, thereby improving quality of life or extending life. Nevertheless, anti-fibril therapies are actively being investigated in clinical trials to evaluate their ability to complement and synergize with current SoC.